UPAYA PENYEMBUHAN RUAM POPOK (DIAPER RASH) MENGGUNAKAN VCO (VIRGIN COCONUT OIL) - Eny Susanti (NHM PRESS, 2020)
In the treatment of infants and toddlers , at this time now diapering infants and toddlers is the most practical , effective , and hygienic to hold urine ( urine ) and feces ( stool ) not to spread at the time of urination or defecation , But in fact , the skin of infants and toddlers are not ready to adapt to circumstances that may arise as a result of prolonged contact with urine and feces caused by the use of diapers .The purpose of this study is influence analyzing gift VCO against Diaper rash to infant 0-2 years at the middle of mandangin island are of work Puskesmas Banyuanyar Sampang. This study design use the Pre Experimental Group One approach is to pre -posttest design . These populations are infants aged 0-2 years in Central Mandangin Island Puskesmas Subdistrict Banyuanyar Sampang and sample 23 with simple random sampling technique . Gathering data using questionnaires and observation , analysis and cross tabulated in univariate and bivariate ( pariet t - test) with a significance value of 0.05 . Before being given a VCO ( Virgin Coconut Oil ) most nearly half of diaper rash before given VCO moderate and severe as many as 10 respondents ( 43 % ) , while after doing given VCO ( Virgin Coconut Oil ) majority of diaper rash after being given mild VCO as many as 12 respondents ( 53 % ) . Results of univariate statistical tests showed Shapiro Wilk normality test 0.667 > 0.005 , which means normal distribution , then the Test Bivariat used are Paired T Test and test results Paired T Test = 0,000 ie < 0.05, which means that influence gift VCO against Diaper rash to infant 0-2 years at the middle of mandangin island are of work Puskesmas Banyuanyar Sampang. With the public better understand the importance of the care and treatment of diaper rash . In addition, the public can take advantage of VCO ( Virgin Coconut Oil ) for the treatment of diaper rash.